Trajectory planning and execution in the workspace for a Delta robot (2016)
This paper describes a technique for trajectory planning and execution in Cartesian Space to be applied in a delta robot. In order to configure and generate the desired path, is designed a software with Graphical User Interface (GUI), in which, the proposed algorithm is implemented to calculate and display the robot movement through midpoints in the workspace.To validate the generated path is used a Delta robot designed and built in the Colombian Robotics Laboratory at Nueva Granada Military University. This robot is controlled by an electronic circuit that enables the proper implementation of the proposed technique. That makes it possible to validate the trajectories calculated by the algorithm and displayed in the simulation software, using a real robot.